A Locus Encompassing the Epstein-Barr Virus bglf4 Kinase Regulates Expression of Genes Encoding Viral Structural Proteins - El-Guindy, Ayman (Public Library of Science, 2014)
The mechanism regulating expression of late genes, encoding viral structural components, is an unresolved problem in the biology of DNA tumor viruses. Here we show that BGLF4, the only protein kinase encoded by Epstein-Barr virus (EBV), controls expression of late genes independent of its effect on viral DNA replication. Ectopic expression of BGLF4 in cells lacking the kinase gene stimulated the transcript levels of six late genes by 8- to 10-fold. Introduction of a BGLF4 mutant that eliminated its kinase activity did not stimulate late gene expression. In cells infected with wild-type EBV, siRNA to BGLF4 (siG4) markedly reduced late gene expression without compromising viral DNA replication. Synthesis of late products was restored upon expression of a form of BGLF4 resistant to the siRNA. Studying the EBV transcriptome using mRNA-seq during the late phase of the lytic cycle in the absence and presence of siG4 showed that BGLF4 controlled expression of 31 late genes. Analysis of the EBV transcriptome identified BGLF3 as a gene whose expression was reduced as a result of silencing BGLF4. Knockdown of BGLF3 markedly reduced late gene expression but had no effect on viral DNA replication or expression of BGLF4. Our findings reveal the presence of a late control locus encompassing BGLF3 and BGLF4 in the EBV genome, and provide evidence for the importance of both proteins in post-replication events that are necessary for expression of late genes.